2019
DOI: 10.1016/j.ccell.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Signature Analysis Reveals NTHL1 Deficiency to Cause a Multi-tumor Phenotype

Abstract: Graphical Abstract Highlights d Biallelic germline NTHL1 mutations predispose to a multitumor syndrome d Biallelic germline NTHL1 mutation carriers are at risk for breast cancer d Tumors from NTHL1-deficient patients reveal a cross-cancer NTHL1-associated signature d Mutational signature analyses can assist to identify germline DNA repair defects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
114
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(138 citation statements)
references
References 34 publications
7
114
0
4
Order By: Relevance
“…Other genes, such as PPM1D, ERCC3, BAP1, and NTHL1 have been reported in BC/OC families [117,[261][262][263][264][265][266], but further studies are needed to confirm these associations.…”
Section: Other Emerging Genesmentioning
confidence: 97%
“…Other genes, such as PPM1D, ERCC3, BAP1, and NTHL1 have been reported in BC/OC families [117,[261][262][263][264][265][266], but further studies are needed to confirm these associations.…”
Section: Other Emerging Genesmentioning
confidence: 97%
“…NTHL1 (Nth‐Like DNA Glycosylase 1) encodes a glycosylase involved in the DNA base excision repair (BER) pathway. Biallelic inactivation of this gene has been associated with the predisposition to attenuated adenomatous polyposis, CRC and other tumor types, being the presence of multiple primary tumors characteristic of the associated syndrome (Belhadj et al, ; Broderick et al, ; Grolleman et al, ; Groves, Gleeson, & Spigelman, ; Rivera, Castellsagué, Bah, van Kempen, & Foulkes, ; Weren, Ligtenberg, et al, ). To date, a total of 33 NTHL1 biallelic carriers belonging to 21 unrelated families have been reported (Table S3).…”
Section: The Prevalence Of Biallelic Nthl1 Mutations Among Unexplainementioning
confidence: 99%
“…biallelic carriers belonging to 21 unrelated families have been reported (Table S3) (48.5%) exhibited multiple primary tumors either in the colorectum or extracolonic. All biallelic carriers that underwent colonoscopy screening (n = 28) were diagnosed with adenomatous polyps (range: 1-200) and five of them (18%) were additionally diagnosed with more than four hyperplastic polyps (range: 4 to >30) (Belhadj et al, 2017;Broderick et al, 2017;Fostira et al, 2018;Grolleman et al, 2019;Rivera et al, 2015;Weren, Ligtenberg, et al, 2015; Table S3).…”
Section: The Prevalence Of Biallelic Nthl1 Mutations Among Unexplaimentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, NTHL1 deficiency could lead to severe mutagenesis. Indeed, it has been reported that NTHL1 deficiency is highly mutagenic and promotes adenomatous polyposis and colorectal cancer (22).…”
mentioning
confidence: 99%